Methodology to design district heating systems with respect to local energy potentials, CO2-emission restrictions, and federal subsidies using oemof - Kersten, Mathias; Bachmann, Max; Guo, Tong; Kriegel, Martin (International Journal of Sustainable Energy Planning and Management, 2021)
To combine a variety of different heat generating technologies, static design methods will not be sufficient to design future heat supply systems. New energy system design approaches are being developed with consideration of fluctuating renewable energy sources, different subsidy measures, as well as CO2-emission reduction targets. The motive of this study is to develop a new methodology to design and optimise an energy system considering these constraints. The methodology is developed based on the Open Energy Modelling Framework (oemof) and applied on a sub-urban region in northern Germany. Local specifics of energy source potentials are taken into account. It adapts the boundary conditions of a German federal funding program for innovative heat supply networks “Heating Network Systems 4.0.” Federal funding restrictions of combined heat and power systems and self-consumption are also considered. An economic optimisation was conducted considering a variety of energy sources. Cost optimal energy system design was computed regarding investments costs, energy prices and annual CO2-emission restrictions. The integration of combined heat and power (CHP), photovoltaic (PV) and heat pump (HP) systems in combination with storage size optimisation can reduce CO2-emission of heat production by approx. 69% compared to the current state of heat production.